Physicochemical characterization of natural honeys from different regions in Slovakia - Sudzina, Marian (2009)
This study is intended to determine the physicochemical characteristics of Slovakian honeys, and compare them with specifications described in the Codex Alimentarius Standard, the European Honey directive, the Slovak Codex Alimentarius and Slovak standard No. 1/2006. In addition, we tried to find out correlations between individual constituents of honeys. Physicochemical characterization was carried out following the harmonized methods dictated by the International Honey Commission IHC. Honey samples (n=50) were collected from three honey types (blossom, blends, honeydew), and from the three main Slovakian geographical regions (named 'east', 'middle' and 'west'). The physicochemical evaluation included moisture, reduced sugars, proline, hydroxymethylfurfural (HMF), conductivity, diastase and invertase activity, pH and water activity, following the techniques proposed by the European Honey Commission (EHC). The moisture content in the honey varied from 15.26 to 17.65%, HMF levels ranged from 21.83 to 63.00 mg.kg-1, the diastase activity varied from 21.01 DN to 36.67, invertase activity varied from 121.73 to 164.11 U.kg-1, the proline content varied from 426.56 to 531.79mg.kg-1, the fructose content values were found from 36.33 to 40.20 g.100g-1, the glucose content values ranged from 27.67 to 31.00g.100g-1, the values of saccharose content were from 0.15 to 0.37g.100g-1, the conductivity varied from 29.48 to 97.24mS.cm-1, the pH value varied from 4.06 to 4.80 and the water activity content varied from 0.55 to 0.57. Significant differences (P ≤ 0.05) were found between HMF and fructose, glucose and saccharose and conductivity and pH, significant differences (P ≤ 0.01) between fructose and glucose and significant differences (P ≤ 0.001) were found between HMF and conductivity. Between blossom honey and honeydew honey were found statistical significant differences in HMF (P ≤ 0.05) and conductivity between honeydew honey and blossom honey (P ≤ 0.001). Among regions were determined statistical differences between HMF and invertase (P ≤ 0.05) and conductivity (P ≤ 0.01).